The Role of Automated Information Systems and Technologies in Enhancing the Quality of Education (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article explores the application of automated information systems and technologies in the educational process, with an emphasis on enhancing the quality of education. The authors analyze modern trends in education and examine the benefits that information technologies can bring to teaching and managing the learning process. The article also discusses the use of cloud computing, data analytics, and artificial intelligence to optimize educational methods and personalize learning. Ultimately, the authors conclude that proper implementation of automated information systems can significantly improve the quality of education and contribute to the successful development of students.